The Effect of Management And Utilization of Productive Zakat Towards Mustahiq Empowerment - Romadona Adawiyah; Dinnul Alfian Akbar; Fernando Africano (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2020)
This research aims to discover the influence of management of productive zakah on the mustahiq as the BAZNAS in south sumatra province as well as influence of utilization of productive zakah on the mustahiq empowerment. Data collection method used in this research utilized questionnaire in likert scale.Wherein all of 30 residents (population) are being used as sample (census technique). The F test, t test and the coefficient determinan (R2) the show that management of productive zakah had a positive and significant impact on mustahiq empowerment in (BAZNAS) south sumatra province and utilization of productive zakah had a positive and significant impact on mustahiq empowerment as well.